Analisis Dukungan Manajemen Puncak Terhadap Kualitas Laporan Keuangan dengan SIMDA Sebagai Mediasi - Salsabila Putri Rizki Hapsari; Endah Susilowati (Journal of Management and Bussines (JOMB), 2023)
This research aims to find out what is the influence of top management support on the quality of financial reports with Simda as mediation. This research uses a quantitative research design, primary data as the data source, and questionnaires as the main data collection tool. To evaluate several hypotheses, an analysis method known as Partial Least Squares was used using the WrapPLS 7.0 program. The conclusion is that top management support has an impact on regional management information systems, top management support has an impact on the quality of financial reports, regional management information systems have an impact on the quality of financial reports, and regional management information systems mediate top management support for high quality financial reports. Keywords: Financial Report Quality, Regional Management Information System, Top Management Support